(untitled) (Semiárida, 2020)
The present work was carried out in the experimental field of the Faculty of Agronomy UNLPam. It evaluated the relationship between photosynthetically active radiation (PAR) intercepted by the crop during the critical period and yield of bread wheat (Triticum aestivum l.), durum wheat (Triticum durum l.) and triticale (X Triticosecale Witt). Also evaluated the effect of nitrogen application to tillering. In the first date of sampling (October 3) three varieties of triticale showed increased interception than the varieties of wheat bread and wheat with nitrogen fertilizer. The variety of wheat bread "Baguette P13" had increased interception in control. On remaining dates of sampling the varieties of the three species had an unlike behavior, although the varieties of durum wheat were lower PAR interception. The addition of nitrogen to tillering significantly improved the percentage of PAR interception. The yield of the modern varieties of wheat bread was bigger than the ancient ones, being explained by a major IC, more than for major PAR interception. The addition of nitrogen compensated the yield fall when the flowering date more lately. Director: Fernández, Miguel Angel